Geranylation of benzoic acid derivatives by enzymatic extracts from Piper crassinervium (Piperaceae) - Lopez, Silvia Noeli [UNESP]; Lopes, Adriana Aparecida [UNESP]; Batista, Joao Marcos [UNESP]; Flausino, Otavio [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Kato, Massuo Jorge; Furlan, Maysa [UNESP] (Elsevier B.V., 2010)
The ability to carry out geranylations on aromatic substrates using enzymatic extracts from the leaves of Piper crassinervium (Piperaceae) was evaluated. A literature analysis pointed out its importance as a source of prenylated bioactive molecules. The screening performed on aromatic acceptors (benzoic acids, phenols and phenylpropanoids) including geranyl diphosphate as prenyl donor, showed the biotransformation of the 3,4-dihydroxybenzoic acid by the crude extract, and the p-hydroxybenzoic acid by both the microsomal fraction and the crude extract, after treating leaves with glucose. The analysis of the products allowed the identification of C- and O-geranylated derivatives, and the protease (subtilisin and pepsin) inhibition performed on the O-geranylated compounds showed weak inhibition. Electrophoretic profiles indicated the presence of bands/spots among 56-58 kDa and pI 6-7, which are compatible with prenyltransferases. These findings show that P. crassinervium could be considered as a source of extracts with geranyltransferase activity to perform biotransformations on aromatic substrates. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Piper crassinervium; Piperaceae; Biotransformation; Geranylation